Impact of Financial Risks on the Performance of Regional Development Banks in Indonesian: A Comprehensive Analysis of ROA and ROE - Darmansyah; Juniar, Asrid (Yayasan Ilomata, 2024)
This research analyzes the simultaneous, partial and dominant influence on financial risk factors on the performance of regional development banks in Indonesia. The population and sample of this study is a panel data set of 27 Regional Development Banks (RDB) in Indonesia from 2019 to 2023 from the annual financial reports. The results show that financial risk has a significant influence on ROA (74.5%) and ROE (61.3%). Also Liquidity Risks, Market Risks, Operational Risk and Leverage Risk significantly affect Return on Assets. Return on Equity is only affected by Liquidity Risks and Market Risks.